Emissive tetraphenylethylene (TPE) derivatives in a dissolved state tightly fastened by a short oligo(ethylene glycol) chain. Issue 18 (13th August 2020) - Tanaka, Yuma; Machida, Takashi; Noumi, Toshiaki; Sada, Kazuki; Kokado, Kenta
Abstract : The requirements for strong emission from a typical AIEgen in solution were quantitatively examined both by photochemical experiments and theoretical computations. Abstract : The structural change in the excited state evidently plays a crucial role in the quenching process of organic molecules exhibiting aggregation-induced emission (AIE, thus AIEgens) in the solution state. In this report, we synthesized a series of tetraphenylethylene (TPE) macrocycles having a covalent oligoethylene glycol (OEG) linkage between vicinal phenyl rings with various chain lengths and substituting positions. As a result, the obtained TPE macrocycles which are tightly fastened by short OEG chains showed strong emission even in the solution state. The tight fastener efficiently restricted the π twist around the central CC bond in TPE macrocycles, which was also supported by theoretical computations. These results provide very important information about the origin of the AIE properties of TPE derivatives, which will lead to the rational design of new AIEgens.